1926
DOI: 10.1172/jci100066
|View full text |Cite
|
Sign up to set email alerts
|

Guanidine Excretion in Relation to Hypertension

Abstract: A series of observations haveLeen made recently, the resultscf which suggest, a relationship between arterial hypertension and guanidine metabolism. Major and Stephenscn (1) studyipg the influence of certain urinary constituents on blood pressure, noted that methyl guanidine, a product of normal metabolism and a constituent of normal urine, had marked pressor effects. These authors suggested that this compound, if produced in excess or imperfectly excreted, might account for increased blood pressure. Creatinin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1926
1926
2012
2012

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Our observations (also see Dataset S1 ) indicated that (a) dialysis/desalting through all MWCO devices, down to 2 KDa, abrogated the inhibitory effect of urine similarly ( Figure S2A ); (b) concentration of urine did not worsen its inhibitory effect, likely due to passage of the inhibitory molecules through 3–5 KDa MWCO membranes of the concentrator (data not shown); (c) acidification, alkalinization, EDTA treatment, or boiling/centrifugation of urine did not alleviate inhibition, suggesting that the inhibitor was a small (<2 KDa) molecule, not related to inherent acidic pH of normal urine (and not influenced by alkalinization), not likely a divalent cation, and not protein in nature ( Figure S2B ). Interestingly, at supra-physiological concentrations [25] – [27] , a mix of chaotropic molecules (urea, guanidine) and common ions in urine was significantly inhibitory as an EPA293 diluent (PBS vs. Mix, EC 50 comparison; p = 0.0005, F-test) ( Figure S2C ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our observations (also see Dataset S1 ) indicated that (a) dialysis/desalting through all MWCO devices, down to 2 KDa, abrogated the inhibitory effect of urine similarly ( Figure S2A ); (b) concentration of urine did not worsen its inhibitory effect, likely due to passage of the inhibitory molecules through 3–5 KDa MWCO membranes of the concentrator (data not shown); (c) acidification, alkalinization, EDTA treatment, or boiling/centrifugation of urine did not alleviate inhibition, suggesting that the inhibitor was a small (<2 KDa) molecule, not related to inherent acidic pH of normal urine (and not influenced by alkalinization), not likely a divalent cation, and not protein in nature ( Figure S2B ). Interestingly, at supra-physiological concentrations [25] – [27] , a mix of chaotropic molecules (urea, guanidine) and common ions in urine was significantly inhibitory as an EPA293 diluent (PBS vs. Mix, EC 50 comparison; p = 0.0005, F-test) ( Figure S2C ).…”
Section: Resultsmentioning
confidence: 99%
“…To further identify the chemical nature of the inhibitor, we tested several chemical treatments on urine (10 m boiling followed by centrifugation; alkalinization (pH 8) with sodium hydroxide; acidification (pH 5) with glacial acidic acid; and addition of 5, 10 or 20 mM EDTA), and used the treated urines as EPA293 diluents in sELISA. In addition, we tested known chaotropic molecules present in urine, such as urea and guanidine (guanidine hydrochloride), and divalent cations (known kosmotropes) calcium (Calcium chloride) and magnesium (Magnesium chloride), individually or combined in PBS (pH 6, 7.2 or 7.4) at physiological or supra-physiological levels (final concentration ranges: 50–800, 1–8, 1–20 and 1–20 mmol/L, respectively) [25] – [27] . All chemical reagents used were from Sigma-Aldrich, St. Louis, MO.…”
Section: Methodsmentioning
confidence: 99%